Таня Гроттер и проклятие некромага: повесть / Д. А. Емец - Емец Дмитрий (Таня Гроттер, 2008)
Экземпляры: ф.1 (2008) / Инвентарный номер: 52254 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Е 60 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-445